Fabrication of nanoporous gold and the application for substrate bonding at low temperature. (15th January 2015) - Wang, Wei-Shan; Lin, Yu-Ching; Gessner, Thomas; Esashi, Masayoshi
Abstract: MEMS-compatible fabrication of nanoporous gold and the application for low temperature bonding are demonstrated. A cyanide-free electroplating solution is prepared for the Au–Sn alloy deposition. To investigate the influence of electroplating on Au–Sn alloy and nanoporous gold, different plating parameters and various sizes of patterns are designed and discussed. The optimized electroplating condition realizes 40 to 720 µm line width patterns fabricated on the same substrate. Low temperature substrate bonding at 200 °C is achieved with nanoporous gold and gold film, which has shear bond strength more than 60 MPa. The fracture inspection of the bonded area after shear tests verifies the bonding success. This study gives a study for fabricating on-chip nanostructure, and the results indicate the high feasibility of nanoporous gold for low temperature substrate bonding.